Penerapan Metode Brainstorming Dalam Mengembangkan Kemampuan Berfikir Kritis Pada Mata Pelajaran PAI - Siti Choirun Nafi’ah; Ahmad Saiful Rizal; Achmad Abdul Azis (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study was motivated by the low level of students’ critical thinking skills in the learning process of Islamic Religious Education and Character (PAIBP) at SMKN 2 Blora. Therefore, an appropriate learning method is needed to encourage student participation and develop critical thinking skills, one of which is the brainstorming method. This study aims to describe the implementation of the brainstorming method in PAIBP learning, examine the development of students’ critical thinking skills after the implementation of the method, and identify the supporting and inhibiting factors in its implementation. This research employed a qualitative approach with data collection techniques including observation, interviews, and documentation. The results show that the implementation of the brainstorming method was carried out through several stages, namely providing problem stimuli, collecting ideas freely, grouping and clarifying ideas, and drawing conclusions together. The application of this method was able to increase students’ active participation and encourage the development of critical thinking skills in PAIBP learning. Supporting factors include teacher readiness, students’ enthusiasm, and a conducive classroom atmosphere, while the inhibiting factors include limited learning time and differences in students’ self-confidence levels.